Kajian Proses Adaptasi Narasi Visual "Scott Pilgrim Vs The World" dari Komik Menjadi Film - Sophia Purbasari; Alvanov Zpalanzani Mansoor; Acep I. Saidi (Wimba : Jurnal Komunikasi Visual, 2013)
Film and comic are visual narrative media which emphasize visual elements in delivering its message towards its audiences. Although both media emphasize similar elements, but in comic adaptation movies, there are several changes in visual narrative structure. The research object, Scott Pilgrim VS The World is analyzed through structural adaptation analysis in order to understand the specific aspects of structural changes. The changes are analyzed especially from four elements of visual narrative aspects from both media, which are narration, layout, image, and sound. The overall adaptation processes in Scott Pilgrim VS The World are emphasized in pictorial sequence changes which heavily influenced other visual structure elements. The visual sequence compression in adapting the story from comic to movie while maintaining the story essence is the fundamental adaptation process.